Wildlife of the deserts - Wagner, Frederic H. (New York : H. N. Abrams, 1980)
Text and illustrations describe the desert environment, topography, and the wildlife that survive in it.
"A Chanticleer Press edition.".
Booklist.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Desert biology; Deserts